Effect of EPR coefficient policy on the production decision in precious metal accessory recycling. Issue 4 (16th February 2017) - Li, Yongjian; Niu, Shuiye; Zhao, Xiukun; Wang, Wen
Abstract : This study examines the effect of the extended producer responsibility (EPR) coefficient policy on the production decision between a supplier and a manufacturer in a precious metal accessory recycling supply chain. EPR coefficient is a regulation proposed by the government and enterprises to balance economic profit and EPR behaviour, and refers to the production proportion of recycled products in all serviceable products. Enterprises with a large EPR coefficient have good EPR practice. This study uses the newsvendor model and numerical simulation to study a supply chain system with remanufacturing and reproduction processes. Results show that the optimal recycling mode and the optimal EPR coefficient are always present in precious metal accessory operations. The increasing market demand for recycled products and the improving whole recycling parameters are both effective in enlarging the optimal EPR coefficient. However, the improvement of single or partial recycling parameters (except the market demand parameter) has no effect on the optimal EPR coefficient. The implementation mechanism and applicable conditions of the EPR coefficient policy are also explored. This study indicates that the EPR coefficient policy is an appropriate and effective approach to promote the EPR practice of the Chinese Government.